A comparison of the effects of Chinese non-pharmaceutical therapies for premature ovarian failure: A PRISMA-compliant systematic review and network meta-analysis. Issue 26 (26th June 2020) - Zhang, Jinhuan; Huang, Xingxian; Liu, Yongfeng; He, Yuhai; Yu, Haibo
Abstract: Background: Premature ovarian failure (POF) is commonly treated with hormone replacement therapy (HRT). Many patients with POF choose acupuncture as a complementary therapy over HRT, due to possible adverse reactions. This systematic review and network meta-analysis (NMA) compares the efficacy of different forms of acupuncture therapies for POF. Methods: Seven databases including PubMed, the Cochrane Library, Embase, Wanfang database, China National Knowledge Infrastructure database, VIP Chinese Science, and Chinese Biomedical Database were searched for randomized controlled trials (RCTs) of various acupuncture treatments for POF. This time spanned from the date of database inception to January 13, 2020. RevMan 5.3 was used to assess the bias risk of the studies. A NMA of the included studies was performed using Stata14.0. Results: A total of 408 items were searched in this study, and finally this NMA included 16 RCTS, involving 1, 307 patients. It showed that acupuncture (OR:1.35, 95%1.24 to 1.47) has the best effectiveness among the four acupuncture (standardized mean difference [SMD]-16.30, 95% −31.33 to −1.28) is the most effective and the best in reducing follicle-stimulating hormone levels among the four acupuncture treatments. Acupuncture (SMD 26.67, 95%5.95 to 47.40) and acupoint embedding (SMD41.14, 95%11.90 to 70.37) were ranked in the top 2 positions, in improving estradiol, whereas acupuncture (SMD-4.90, 95% −8.10 to −1.70) was than acupoint embedding and HRT, in reducing luteinizing hormone level. In addition, our conclusions have not changed significantly after the sensitivity analysis. Protocol registration number: CRD42020150508. Conclusion: With clinical evidence summarized by NMA, it is observed that acupuncture is the most promising therapy for improving menopausal symptoms, decreasing serum follicle-stimulating hormone and luteinizing hormone level. Therefore, acupuncture could be effective for patients with POF, who are intolerant to the adverse effects of hormone replacement therapy or who would prefer non-drug therapies. Further multi-center and high-quality RCT studies should be conducted to make our conclusion more rigorous. Abstract : Supplemental Digital Content is available in the text